The main chemical properties of hot and cold mineral waters in Bayankhongor, Mongolia - Oyuntsetseg, D; Uugangerel, E; Minjigmaa, A; Ueda, A (Mongolian Journal of Chemistry, 2014)
In the current study, hot and cold mineral springs and sub mineral waters in the Bayankhongor province were examined for their chemical characteristics and identified cold mineral waters classification according to mineral water classification of Mongolia. The hot spring waters belong to Na+-HCO3- and Na+-SO42- types. The cold mineral spring of Lkham belongs to Ca2+-HCO3- type. All sub mineral waters are generally located in the two areas (northern part or mountain forest area and the southern part or Gobi desert area). TDS concentrations of cold springs of the southern part in the study area were higher than northern part’s cold springs. The total dissolved silica content of cold spring was ranged from 4.5mg/L to 26 mg/L which did not correspond to requirements of mineral water standard of Mongolia. Thus, these cold springs are belonging to sub mineral water classification. The sub mineral waters were characterized into four types such as a Ca2+-SO42-, Na+-SO42-, Na+-HCO3 and Ca2+ - HCO3 by their chemical composition in the study area. The values for the quartz, chalcedony geothermometer and the Na/K geothermometer were quite different. The silica-enthalpy mixing model predicts a subsurface reservoir temperature between 124 and 197°C and most of the hot waters have been probably mixed with cold water. The result shows that an averaged value of calculated temperature ranges from 77°C to 119°C which indicates that studied area has low temperature geothermal resources. DOI: http://doi.dx.org/10.5564/mjc.v15i0.324 Mongolian Journal of Chemistry 15 (41), 2014, p56-62